Through the Glass Darkly: New Paradigms for Counselors, Courage, and Spirituality in Contemporary Education - Goodell, Judy; Robinson, S.J., David C. (Catholic Education: A Journal of Inquiry and Practice, 2008)
This article proposes a paradigm shift in the view of the school counselor role. Evolving from the dualistic mind/body split of traditional physics, counseling has largely focused on problem identification and attempting to fix what is wrong. The new sciences of chaos and complexity invite a more holistic view, with the psychospiritual development of all students seen as an appropriate part of a comprehensive education. School counselors are well placed to mentor the psychospiritual development of all students and to facilitate the presence of spirituality on school sites. Two complementary models, Courage to Teach/Lead and the Ignatian model of Spiritual Discernment are presented with discussion of how their principles and practices might be applied by counselors engaged in this role shift.